Long-term Survival Analysis of Robotic Versus Conventional Laparoscopic Hepatectomy for Hepatocellular Carcinoma: A Comparative Study. Issue 2 (April 2016) - Lai, Eric C. H.; Tang, Chung Ngai
Abstract : Purpose: Robotic partial hepatectomy has been advocated as an alternative to conventional laparoscopic partial hepatectomy, but studies supporting the efficacy or oncological outcomes of robotic partial hepatectomy are scarce in the last decade. Methods: This study compared the long-term oncological outcomes of robotic (n=100) and conventional laparoscopic hepatectomy (n=35) for hepatocellular carcinoma (HCC). Results: Robotic group had a significant higher proportion of major hepatectomies (27% vs. 2.9%) and tumors located at or across posterosuperior segments (29% vs. 0%) than conventional laparoscopic group. For the perioperative outcomes, robotic group had a significant longer mean operation time (207.4 vs. 134.2 min). Both groups had similar blood loss (334.6 vs. 336 mL). There was no difference in morbidity (14% vs. 20%) and mortality rate (0% vs. 0%). Concerning oncological outcomes, there was no difference between 2 groups in R0 resection rate (96% vs. 91.4%), 5-year overall survival (65% vs. 48%), and disease-free survival (42% vs. 38%). Conclusions: Robotic approach is an acceptable alternative to laparoscopic partial hepatectomy for HCC. With the potential advantages of robotic system in performing major hepatectomy and resection of tumor in difficult segments, robotic surgery may have an impact on the therapeutic strategy of HCC.